IMPROVING SIXTH GRADE STUDENTS’ LANGUAGE LITERACY BY UTILIZING DIGITAL MULTILINGUAL THEMATIC DICTIONARY - Candra Dewi, Ni Putu Eka; Ratminingsih, Ni Made; Santosa, Made Hery (Universitas Suryakancana, 2024)
This recent study examines the impact of the Digital Multilingual Thematic Dictionary in improving students’ literacy skills; ability to read and write which built from vocabulary. The findings of this research are expected to show a significant impact after the application of digital multilingual thematic dictionaries in improving students' literacy skills. Kurt Lewin’s Classroom Action Research (CAR) consist of planning, acting, observing, and reflecting was employed in this study. The subject of this study was sixth-grade students of SD N 3 Banjar Jawa in the first semester of 2023/2024, which involved one class with a total of 30 students. The instrument used in this current research were literacy skill tests which include pre-test and post-test questions. The results of this study were analyzed with quantitative descriptive using descriptive statistical analysis. The descriptive statistics analysis was carried out with the aim of knowing the mean, median, mode, and dispersion which includes range, standard deviation and variance. The result of this study was based on the improvement in each student score from pre-test, post-test 1 and post-test 2. The research finding showed that the use of the Digital Multilingual Thematic Dictionary significantly improves language literacy skills of sixth-grade students. Thus, it can be concluded that Digital Multilingual Thematic Dictionary can improve students’ language literacy skills.